Analisis Faktor-Faktor Penyebab Proses Persalinan Secara Caesar Menggunakan Algoritma Id3 Dengan Metode Decision Tree - Shahar, Niski Robi, Yusuf Sulistyo Nugroho, S.T., M.Eng (2016)
Childbirth by caesarean section (Sectio Caesarea) is defined as the process of the birth of the baby by making an incision in the abdominal and uterine wall. Caesarean at specific medical indication when normal childbirth can no longer do. This study aims to determine the factors that led to the birth process done by Caesarean (sectio caesarea) in Rumah Sakit Islam PKU Muhammadiyah Adiwerna Tegal. The data mining method used in the determination of this childbirth process using ID3 decision tree algorithm. Attributes used consisted of fetal distress, birth, blood pressure, position of the baby, narrow hips and a Caesarean. In conducting this analysis is using statistical software RapidMiner 5 to determine the factors that most influence the delivery process. The population is all patients who childbirth at RSI PKU Muhammadiyah Adiwerna between 2014-2015 as many as 2052 respondents. The sample was 334 respondents drawn using formulas of slovin. The result of the study shows that the most influence factor in improving the caesarean is fetal distress. This was proved in the decision tree that states fetal distress is specified as the root node, and the last intenal node is the position of the baby. So for health workers in the decision-making process of determining caesarean, it is better to see from fetal distress as the main factor